APLIKASI PRINSIP GESTALT PADA LOGO LPI SALSABILA - Budi Yuwono (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2021)
Gestalt principles derived from Psychology have been adopted and applied to Visual Communication Design. They are visual perception perspectives seeing a series of individual elements as a whole. Therefore, the purpose of visual communication conveyed by the communicator will be perceived with the same meaning for the communicant. In this study, the logo of Salsabila educational institution was observed. The geometric elements in the logo were collected based on their proximity and similarity in shapes and colours. The logo was then investigated using qualitative research methods referring to the gestalt principles